Effect of temperature on catalytic hydrocracking of Xiaolongtan lignite over a mesoporous silica-coated Fe3O4 supported magnetic solid base for producing aromatics. (February 2021) - Liu, Fang-Jing; Guo, Jia-Pei; Liu, Guang-Hui; Bie, Lei-Lei; Zhao, Yun-Peng; Huang, Zai-Xing; Wei, Xian-Yong
Abstract: Lignites are promising candidates as feedstocks for producing chemicals rather than used as solid fuels. Herein, a mesoporous silica-coated Fe3 O4 supported magnetic solid base (MSB) was prepared for catalytic hydrocracking (CHC) of Xiaolongtan lignite (XL). The effect of reaction temperature on aromatic production through CHC was investigated. The results showed that the MSB with abundant mesoporous structures has strong basic sites and superparamagnetism, which can effectively enhance producing soluble portions and aromatics from hydrocracking of XL. Both the yields of the soluble portions and aromatics from CHC of XL increased with raising reaction temperature. The maximum yield of the soluble portions reached 78 wt% at 300 °C from CHC. Phenols are the main group component from CHC of XL at 300 °C, which could be mainly generated from the cleavage of C–O bridged bonds in XL. Both the yields of phenols and arenes from CHC at 300 °C are twice more than those from CHC. It was proposed that the MSB could catalyze splitting H2 to release active H − and facilitate H − transfer to cleave the C–O bridged bonds, resulting in producing higher yields of aromatics. Graphical abstract: Image 1 Highlights: The prepared magnetic solid base (MSB) has strong basicity and superparamagnetism. MSB present good activity for catalytic hydrocracking (CHC) of Xiaolongtan lignite. The yields of soluble portions and aromatics increased with raising temperature. The CHC produced much higher yields of phenols and arenes than non-CHC at 300 °C. The MSB facilitated cleaving C –O bridged bond in lignite to produce more aromatics.